THE CHARACTERISTICS AND REPRODUCTIVE PERFORMANCE OF ETAWA CROSSBRED GOATS IN PALANGKA RAYA - Asri Pudjirahaju; Heri Sujoko; siti ma'rifah; Diah Puspita Anggraeni; Tiara Purnama Sari (Buletin Veteriner Udayana, 2025)
The Etawa crossbred goat is a hybrid breed developed by crossing Etawa males with local Kacang goats to enhance the productivity of the native goat population. This dual-purpose breed is esteemed for its milk and meat production. This study aimed to elucidate the characteristics and reproductive performance of Etawa crossbred goats in Palangka Raya. A survey methodology was employed, with sampling locations selected based on the goats population density. Data collection comprised both primary and secondary data sources. Primary data were acquired through direct observations and interviews with the farm owners. Respondents were selected based on the following criteria: (1) a minimum of three years of goat farming experience and (2) ownership of at least five goats that had previously given birth. The findings from five Etawa crossbred goat farms in Palangka Raya City indicated that the reproductive performance of Etawa crossbred goats was generally favorable. The age at first mating was 16.8 ± 2.68 months, with a pregnancy rate of 70–80%. On four farms, all births were 100% singletons, whereas one farm recorded 50% twin births. The average litter size was 1.16 ± 0.03. The postpartum mating interval was 3 ± 1.22 months, and the kidding interval was 7.80 ± 2.68 months. Pre-weaning mortality ranged from 5% to 6% of kids born on each farm. These findings underscore the necessity for enhanced mating management, particularly comprehensive reproductive record-keeping, to support future selection and productivity improvements in Etawa crossbred goat herds.